Indications of Caesarean Section - Study of 100 cases in Mymensingh Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2012)
This study was a prospective descriptive one. It was done in MMCH from January 1996 to march 1996. A total of 714 deliveries occurred of which 225 deliveries by Caeserean section, incidence of LSCS was 30.36%. The commonest age group of patients being operated ranged from 20 - 30 yrs (77%). Most of the patients who had undergone LSCS were multigravida (45%). The section were due to various indications, the commonest cause in this study was previous caesarean section, foetal distress and obstructed labour. The rate of primary section was more (84%) while repeat section being 16%. The peak range of operations were done in patients with 5 feet 2 inches height. The rate of elective operation was 37% . where emergency operations were done in 63% of cases. Regarding foetal outcome. 92% survived and 8% had perinatal death. DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12167 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.6-10